PENTINGNYA EDUKASI PENGGUNAAN GADGET DALAM MENGATASI MASALAH SOSIAL TERHADAP PENINGKATAN PENDIDIKAN KARAKTER DAN MORAL SISWA - Ihsan, Muzhir; Nurerisna, Siti; Meizia, Revanda Shiva; Framesti, Aldya; Mawahdah, Sarah (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
The use of gadgets always has an impact on the development of children's behavior, because gadgets have various interesting, varied, and flexible features and applications so that they can increase the appeal for everyone, especially among children. Nowadays, gadgets can have a negative impact on the development of children's behavior. Behavioral changes that tend to be negative where as a result of playing gadgets children become easily angry, rebellious, lazy to learn, and can imitate behavior in gadgets. Children have now become active consumers where many electronic products and gadgets make children their market. Gadgets are expected to provide benefits to their users, where users must be able to operate gadgets properly, know the function of gadgets, and know the benefits of gadget applications.